Hellenistic and Roman terracottas in the Cypriot collection of the Ashmolean Museum, Oxford: contexts, iconography, meaning and Mediterranean connections - Ulbrich, A (Brill, 2019)
This article discusses Late Classical to Hellenistic and possibly Roman terracottas in the Ashmolean’s collection of Cypriot antiquities, most of them hitherto unpublished. Presented in rough chronological order by provenance, context and iconographic types, their production techniques, iconographies and styles will be analysed. This reveals that on the one hand, deeply rooted Cypriot traditions, which had incorporated influences from neighbouring regions of the Mediterranean for centuries, were maintained, while, on the other hand, new Late Classical and Hellenistic influences from the wider Greek world were adopted and adapted selectively. By the end of the Hellenistic period, terracotta figurine production in Cyprus was firmly integrated into the eastern Mediterranean Hellenistic koine.